KORELASI PERAN HAKAM (JURU DAMAI) DENGAN MEDIATOR DALAM PROSES MEDIASI PERKARA PERCERAIAN DI PENGADILAN AGAMA - Suwardi Suwardi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2020)
Mediation that is carried out by the mediator in a juridical manner must be carried out before the main examination of the case, and if it is not implemented it will result in the decision being null and void (Supreme Court Regulation Number 1 of 2008). Meanwhile, the legal process that originates from each family party, juridically it is an initiative of the panel of judges to implement (Law on Religious Courts), because in the existing regulations it is stated with the phrase